Pengaruh Karakteristik Komite Audit terhadap Manajemen Laba - Azka Fairuzza; Sri Murni; Halim Dedy Perdana (Jurnal Akuntansi dan Bisnis, 2014)
This study aimed to get empirical evidence from the influence of audit committee characteristics to earnings management. The dependent variable in this study is proxied by earnings management discretionary accruals while the independent variable is audit committee characteristic which proxied by the size of the audit committee, the number of meetings, independent members and financial expertise. Samples are companies listed on the Indonesia Stock Exchange in 2013, with using purposive sampling method. Data analysis using multiple regression model and descriptive statistics. Statistical analysis showed that the size of the audit committee, the number of meetings, independent audit committee members and financial expertise negatively affect discretionary accruals.